The management of desmoid tumours: A joint global consensus-based guideline approach for adult and paediatric patients. (March 2020) - ,; Alman, Ben; Attia, Steven; Baumgarten, Christina; Benson, Charlotte; Blay, Jean-Yves; Bonvalot, Sylvie; Breuing, Jessica; Cardona, Ken; Casali, Paolo G.; van Coevorden, Frits; Colombo, Chiara; et al.
Abstract: Desmoid tumor (DT; other synonymously used terms: Desmoid-type fibromatosis, aggressive fibromatosis) is a rare and locally aggressive monoclonal, fibroblastic proliferation characterised by a variable and often unpredictable clinical course. Previously surgery was the standard primary treatment modality; however, in recent years a paradigm shift towards a more conservative management has been introduced and an effort to harmonise the strategy amongst clinicians has been made. We present herein an evidence-based, joint global consensus guideline approach to the management of this disease focussing on: molecular genetics, indications for an active treatment, and available systemic therapeutic options. This paper follows a one-day consensus meeting held in Milan, Italy, in June 2018 under the auspices of the European Reference Network for rare solid adult cancers, EURACAN, the European Organisation for Research and Treatment of Cancer (EORTC) Soft Tissue and Bone Sarcoma Group (STBSG) as well as Sarcoma Patients EuroNet (SPAEN) and The Desmoid tumour Research Foundation (DTRF). The meeting brought together over 50 adult and pediatric sarcoma experts from different disciplines, patients and patient advocates from Europe, North America and Japan. Highlights: Active surveillance is the well-established primary approach to primary/recurrent sporadic/familial desmoid tumours (DT). Surgery is the accepted second-line treatment only for sporadic tumour DT located in the abdominal wall failing observation. Medical therapies are the second-line treatments for sporadic tumour DT located at all other sites and for all familiar tumour DT failing observation. Local ablative treatments such as cryotherapy or radiotherapy are options that can be considered as an alternative to medical therapies on an individual basis. Pain control is paramount to improve quality of life, independently of the use of active treatment against the disease.